Transformational Leadership Style and Information Communication Technology - Afshari, Mojgan; Abu Bakar, Kamariah; Wong, Su Luan; Foo, Say Fooi; Abu Samah, Bahaman (Eurojournals, 2007)
Without the support of school principals, the educational potential of Information and Communication Technology may not be realized. Principals play a vital role in promoting ICT use in school. Hence, they should have the ability to effectively use technology as a communication tool, a management tool, and a decision making tool. The effective use of these tools can help principals increase their instructional and managerial efficiency. A wide range of factors has been found to affect principals’ use of ICT. Of these, transformational leadership style has been identified as being one of the most important. However little is known about this style and ICT use by principals. This paper, therefore, reviews empirical and selected conceptual research on the role of principals in ICT implementation, factors which influence ICT use and transformational leadership style. Researchers and school leaders will find this information useful in developing their own inquiry and improving their understanding of this important management issue.